EFFECT OF PENTAGAMAVUNON-0 TO THE THEOPHYLLINE PHARMACOKINETICS IN RATS - Hakim, Arief Rahman; Hakim, Lukman; Margono, Supardjan A. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
The research was aimed to observe pentagamavunon-0 activities to theophylline pharmacokinetics in rats. The study of interaction pentagamavunon-0 and theophylline was conducted employing a completely randomized design using male Wistar rats which were divided into 5 groups (6 rats for each group). The groups were given a single oral theophylline 25 mg/kg BW as a control group and were administered single oral pentagamavunon-0 2, 5, 10 and 40 mg/kg BW each dose 4 hours before treatment with theophylline. Serial blood samples (0,2 ml) were withdrawn at various interval via the tail vein for HPLC analysis of unchanged theophylline in blood. The concentration of theophylline was determined based on a standard curve. The concentration-time data determines theophylline pharmacokinetics i.e. Ka, Cmaks, tmaks, AUC0-, Vdss, t1/2 elimination, Clt and MRT. The results indicated that pentagamavunon-0 was found to be able to decrease theophylline clearance 40-51% (P<0.05). The decrease in clearance causes the prolonged life of theophylline in the body.Key words : Pentagamavunon-0, Theophylline, Pharmacokinetics